ANALISA PENGARUH KUALITAS PELAYANAN INTERNAL TERHADAP KINERJA KERJA KARYAWAN KOPERASI TAKSI DI INDONESIA - Yolanda Masnita Siagian (Media Riset Bisnis & Manajemen, 2003)
This paper suggests that to deliver high levels of customer satisfaction, organizations must identify, measure, and manage the internal elements that produce it. Intemal service quality (defined for this purpose as employee satisfaction with the service received from internal service providers) has received little attention in the empirical literature, yet intemal service quality remains complex, in part because its composition can vary for differentorganizations at different times. In short, which internal services are important, and how important their quality is, depends on an organization's task and employee. Despite this variability, that intemal service quality has basic components important to most organizations. On this paper also explores the relationship between intenal service quality and job satisfaction, one important indication of an organization's work environment. We propose thatinternal service quality is important because it relates to job satisfaction. This relationship may begin to explain the observation that service firms rarely have satisfied customers without having satisfied employees